Novel Rickettsia spp. in two common overwintering North American songbirds. Issue 1 (31st December 2022) - Becker, Daniel J.; Byrd, Allison; Smiley, Tara M.; Marques, Mariana Fernandes; Nunez, Julissa Villegas; Talbott, Katherine M.; Atwell, Jonathan W.; Volokhov, Dmitriy V.; Ketterson, Ellen D.; Jahn, Alex E.; Clark, Kerry L.
ABSTRACT: American robins and dark-eyed juncos migrate across North America and have been found to be competent hosts for some bacterial and viral pathogens, but their contributions to arthropod-borne diseases more broadly remain poorly characterized. Here, we sampled robins and juncos in multiple sites across North America for arthropod-borne bacterial pathogens of public health significance. We identified two novel Rickettsia spp. in one wintering migrant per bird species related to bellii, transitional, and spotted rickettsiae fever groups. Stable isotope analyses of feathers suggested spring migration of these common songbirds could disperse these novel rickettsiae hundreds-to-thousands of kilometers to host breeding grounds. Further work is needed to characterize zoonotic potential of these rickettsiae and host reservoir competence.